Co-voting Democracy - Hans Gersbach (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
We outline a new voting procedure for representative democracies. This procedure should be used for important decisions only and consists of two voting rounds: a randomly-selected subset of the citizens is awarded a one-time voting right. The parliament also votes, and the two decisions are weighted according to a pre-defined key. The final decision is implemented. As this procedure gives the society – represented by the randomly-chosen subset – a better say for important decisions, the citizens might be more willing to accept the consequences of these decisions.
Keywords: D7; D8; 330; Co-Voting; Representative Democracy; Citizen Participation; Legitimacy of Democracy; Assessment Voting; Wahlverhalten; Partizipation; Legitimität; Demokratie; Neue politische Ökonomie; Entscheidungstheorie